Crushed, uncooked egg in the oropharynx: a café coronary? - A. I. Mgbehoma; S. S. Soyemi; J. O. Obafunwa (Egyptian Journal of Forensic Sciences, 2023)
Abstract Background Obstruction of the upper respiratory airway can terminate in fatal asphyxia. Autopsy findings in asphyxial deaths as described in literature are not necessarily pathognomonic. A complete autopsy with ancillary studies is necessary to establish the cause, time, and manner of death. Case presentation The authors present a 44-year-old male who was found dead in his car. He had been remanded in prison for drug trafficking 1 year prior to his death. No other history or death scene findings were provided by the police. Autopsy revealed a crushed, uncooked egg in his oropharynx. Postmortem radiology and toxicology were not done due to nonavailability of the required facilities. Death was ascribed to asphyxia due to a crushed, uncooked egg in the oropharynx. The manner of death could not be ascertained because pertinent information regarding the deceased’s medical records, locus report, and other ancillary investigations was not available. Conclusions This report presents an unusual cause of mechanical upper airway obstruction that has never been documented and discusses some of the deficiencies of autopsy practice in resource-limited countries.